Numerical Investigation of Jet Impingement Cooling of a Flat Plate with Carbon Dioxide at Supercritical Pressures. Issue 2 (20th January 2018) - Chen, Kai; Jiang, Pei-Xue; Chen, Jian-Nan; Xu, Rui-Na
ABSTRACT: Confined round jet impingement cooling of a flat plate at constant heat flux with carbon dioxide at supercritical pressures was investigated numerically. The pressure ranged from 7.8 to 10.0 MPa, which is greater than the critical pressure of carbon dioxide, 7.38 MPa. The inlet temperature varied from 270 to 320 K and the heat flux ranged from 0.6 to 1.6 MW/m 2 . The shear-stress transport turbulence model was used and the numerical model was validated by comparison with experimental results for jet impingement heating with hot water at supercritical pressures. Radial conduction in the jet impingement plate was also considered. The sharp variations of the thermal-physical properties of the fluid near the pseudocritical point significantly influence heat transfer on the target wall. For a given heat flux, the high specific heat near the wall for the proper inlet temperature and pressure maximizes the average heat transfer coefficient. For a given inlet temperature, the heat transfer coefficient remains almost unchanged with increasing surface heat flux at first and then decreases rapidly as the heat flux becomes higher due to the combined effects of the thinner high specific heat layer and the smaller thermal conductivity at higher temperature.